2018
DOI: 10.1186/s12879-018-3040-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic analysis of respiratory viral infections among Singapore military servicemen in 2016

Abstract: BackgroundRespiratory illnesses have been identified as a significant factor leading to lost training time and morbidity among Singapore military recruits. A surveillance programme has been put in place to determine etiological agents responsible for febrile, as well as afebrile respiratory illnesses in a military camp. The goal of the study is to better understand the epidemiology of these diseases and identify potential countermeasures to protect military recruits against them.MethodsFrom Jan 2016 - Jan 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
3
13
0
1
Order By: Relevance
“…Several recent studies have analysed the epidemiologic pattern of respiratory viral infections; Rhinovirus is usually the most common single pathogen found in ARI surveillances samples with prevalence range 24. -50% followed by RSV 22-25% and influenza viruses 7.2-8% either by detection in nasal washes or nasopharyngeal swabs [ 21 ] [ 22 ] [ 23 ], which comes in accordance with an Egyptian study by Amin et al, 2012 RSV virus was detected with a high predominance (51.9%) in Egyptian asthmatic children with acute respiratory tract infection [ 24 ].…”
Section: Discussionsupporting
confidence: 71%
“…Several recent studies have analysed the epidemiologic pattern of respiratory viral infections; Rhinovirus is usually the most common single pathogen found in ARI surveillances samples with prevalence range 24. -50% followed by RSV 22-25% and influenza viruses 7.2-8% either by detection in nasal washes or nasopharyngeal swabs [ 21 ] [ 22 ] [ 23 ], which comes in accordance with an Egyptian study by Amin et al, 2012 RSV virus was detected with a high predominance (51.9%) in Egyptian asthmatic children with acute respiratory tract infection [ 24 ].…”
Section: Discussionsupporting
confidence: 71%
“…Given the relative ranking of virus families in conferring cross-protection, we suggest focusing the search for mechanisms on common factors induced by both adenovirus and influenza virus. Notably, our previous studies suggest that infections with these 2 infections may be more severe, because they are more likely to present with febrile illness [26] and higher temperatures (≥38°C) than infections due to other common circulating virus families [16]. This again supports a cytokine-mediated antiviral effect.…”
Section: Discussionmentioning
confidence: 53%
“…Nine studies containing descriptive epidemiology data from ASEAN countries were identified: two hospital-based studies of children with severe pertussis (Kowalzik et al, 2007;Sadiasa et al, 2017), two hospital-based studies of adults with prolonged cough (Siriyakorn et al, 2016;Koh et al, 2016), two seroepidemiology surveys (Wanlapakorn et al 2016;Son et al 2018), and three studies of multiple etiologies of respiratory illness (Wertheim et al 2015;Barger-Kamate et al 2016;Lau et al 2018) (Table 3). Pertussis disease in ASEAN countries is poorly characterized, partly demonstrated by the fact that only six out of ten countries are represented by these nine studies.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…None of the 224 pneumonia cases tested positive for pertussis by PCR while three (0.34%) cases (two clinically and one PCR-confirmed case) were found in the control group. The Singaporean Army performed respiratory disease surveillance of multiple etiologies of acute respiratory illness (ARI) in servicemen at an army clinic (Lau et al, 2018). Seven out of 2647 (0.264%) cases tested positive for pertussis between 2016 and 2017.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%